2013
DOI: 10.1080/02699931.2012.698982
|View full text |Cite
|
Sign up to set email alerts
|

Anxious ultimatums: How anxiety disorders affect socioeconomic behaviour

Abstract: Although the role of emotion in socioeconomic decision making is increasingly recognised, the impact of specific emotional disorders, such as anxiety disorders, on these decisions has been surprisingly neglected. Twenty anxious patients and twenty matched controls completed a commonly used socioeconomic task (the Ultimatum Game), in which they had to accept or reject monetary offers from other players. Anxious patients accepted significantly more unfair offers than controls. We discuss the implications of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 53 publications
5
50
2
Order By: Relevance
“…This may suggests that while observation may have sensitized the performance monitoring system, this effect was not strong enough to also manifest in overt behavior. In view of evidence for altered behavioral UG performance in individuals with generalized anxiety disorder or panic disorder53, it stands to reason that behavioral effects may only emerge in populations with clinical levels of social anxiety or diagnosed social anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggests that while observation may have sensitized the performance monitoring system, this effect was not strong enough to also manifest in overt behavior. In view of evidence for altered behavioral UG performance in individuals with generalized anxiety disorder or panic disorder53, it stands to reason that behavioral effects may only emerge in populations with clinical levels of social anxiety or diagnosed social anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that anxious traits lead to greater cooperation (Clark et al, 2013) and individuals with anxiety and depressive disorders are more likely to display cooperative behavior (McClure et al, 2007) and accept significantly more unfair offers than healthy controls (Grecucci et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…For example, anxiety disorders are associated with spousal conflict (Whisman, Sheldon, & Goering, ). This social impairment may result from decision‐making biases that lead anxious individuals to choose avoidance strategies in interpersonal situations (Grecucci et al., ). Indeed, levels of anxiety are negatively correlated with the willingness to communicate with strangers (Duronto, Nishida, & Nakayama, ; Samochowiec & Florack, ).…”
Section: Linking Anxiety With Social Decision Makingmentioning
confidence: 99%